Measurement procedure for the assessment of specific absorption rate of human exposure to radio frequency fields from hand-held and body-mounted wireless communication devices. Vector measurement-based systems (Frequency range of 600 MHz to 6 GHz) Part 3, (29th November 2019) - British Standards Institution,
No abstract available